1996
DOI: 10.1177/146642409611600206
|View full text |Cite
|
Sign up to set email alerts
|

Obesity among female university students in the United Arab Emirates

Abstract: The aim of the study was to determine the prevalence of obesity among female students from the United Arab Emirates University. A sample of 566 students was taken. Body weight and height were measured. The students were interviewed to collect data on age, home Emirate, obesity in childhood, obesity among parents, food intake between meals, the consumption of fast foods and physical activity. A student was considered overweight when the body weight was 110-120% of the reference weight of height and was consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
44
2
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 6 publications
11
44
2
1
Order By: Relevance
“…25,26 Certainly, this scenario appears likely in cardiac failure where aerobic training decreases both circulating norepinephrine and NT-proBNP levels. 27 Any such associations are potentially important for UAE nationals since, as in our report, earlier studies suggest that physical activity levels are particularly low in this population 28,29 and may be linked to high levels of obesity and hypertension. 28,30 Regarding our second observation, there is little information, to our awareness, relating circulating levels of the cardiac natriuretic peptides to ethnicity.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…25,26 Certainly, this scenario appears likely in cardiac failure where aerobic training decreases both circulating norepinephrine and NT-proBNP levels. 27 Any such associations are potentially important for UAE nationals since, as in our report, earlier studies suggest that physical activity levels are particularly low in this population 28,29 and may be linked to high levels of obesity and hypertension. 28,30 Regarding our second observation, there is little information, to our awareness, relating circulating levels of the cardiac natriuretic peptides to ethnicity.…”
Section: Discussionsupporting
confidence: 61%
“…27 Any such associations are potentially important for UAE nationals since, as in our report, earlier studies suggest that physical activity levels are particularly low in this population 28,29 and may be linked to high levels of obesity and hypertension. 28,30 Regarding our second observation, there is little information, to our awareness, relating circulating levels of the cardiac natriuretic peptides to ethnicity. In a study of coronary atherosclerosis (as determined by electron beam computed tomography), Abdullah et al 17,31 reported that plasma NT-proBNP levels were slightly, but significantly, lower in African Americans than Caucasians (median 30.6 versus 24.5 pg/ml, Po0.004, n ¼ 1275 and 1394, respectively).…”
Section: Discussionsupporting
confidence: 61%
“…This can explain the high difference between the two studies. We also reported a high prevalence of underweight (13%) especially among young students which confirmed previous results (Musaiger andRadwan, 1995: Amine andSamy, 1996). Musaiger and Radwan reported that 20% of female students were underweight using BMI ≤ 20 as a criterion for underweight which is different from our criterion (BMI ≤ 18.5).…”
Section: Discussionsupporting
confidence: 58%
“…The rates reported in this study are much higher than those reported in Europe but they are close to those reported in Arabian Gulf countries. In the same population (UAEU female students), overweight and obesity were found to be 19% and 9.8% respectively (Musaiger and Radwan, 1995), and in another study Amine and Samy (1996) reported that 10.7% and 34.5% were considered as overweight and obese. Results of obesity reported in the second study are higher than our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation